Investigations on local quartz sand for application in glass industry - Pisutti Dararutana (2018)
© World Scientific Publishing Company. Silica or glass sand is a special type of quartz sand that is suitable for glass- making, because of its high silica content, and its low content of iron oxide and other compounds. In Thailand, deposits of quartz sand are found as the beach and the river sands in many areas; eastern, southern, northeastern and northern. In this work, grain-size distribution and chemical analyses were carried out on 10 sand samples taken from various localities in Thailand such as Chanthaburi, Trat, Rayong, Chumphon, Nakhon Si, Pattani, Phuket, Songkhla, Nong Khai, and Tak provinces. The geological resources show that most of them are the surface-to-near-surface glass sand deposits. The sand grains in most deposits were mainly angular-to-rounded, except in some areas of either angular or rounded grains. Chemical analysis showed that the sands contained more than 95wt% silica and low content of Fe, Al, Ca, Mg, Na, and K. The concentration levels of these components in the samples confirm with internationally acceptable standard for glass production. The quartz sand dressing plants that used the spiral classifier to improve the properties of the quartz sands to meet the standard specifications are mostly located in the eastern area. It can be concluded that most of the quartz sand deposits in Thailand investigated show well-sorted grain-size with considerable purity, i.e. high-grade quality. The advanced works resulted in that these raw quartz sands can be used as raw material for fabrication of soda-lime, lead crystal, and lead-free high refractive index glasses. The colorless and various colored glass products have been satisfactorily used in the domestic art and glass manufactures.